(untitled) (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
Malaria continues to be a significant global health problem, with around 247 million cases and 619,000 related deaths in 2021. In Indonesia, the increase in cases mainly occurred in the eastern region, such as North Penajaman Paser Regency, East Kalimantan. Gender risk factors are also a concern, with men tending to be more susceptible to the disease. This study used a retrospective descriptive method to describe gender risk factors in malaria sufferers in Sepaku in 2021, finding that 96.1% of sufferers were men. These results support previous findings and contribute to the understanding of factors that can aid the development of malaria prevention and control strategies.